2021
DOI: 10.1159/000515904
|View full text |Cite
|
Sign up to set email alerts
|

Gallid Alphaherpesvirus 2 in the Egyptian Turkeys: Molecular Characterization and Establishment of a Universal System for Phylogenetic Classification

Abstract: <b><i>Introduction:</i></b> Gallid alphaherpesvirus 2 (GaHV-2) is a highly contagious oncogenic virus that causes Marek’s disease in chickens and occasionally in turkeys. Among 100 genes identified in GaHV-2 genome, the Meq gene appears to involve viral virulence, oncogenicity, and genetic diversity. Despite the use of Meq gene sequences in phylogenetic classification of GaHV-2 strains circulating in many countries worldwide, no integrated system exists yet. <b><i>Methods:&l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Phylogenetic analyses based on the Meq gene demonstrated that MDV‐1 field strains circulating in Thailand between 2013 and 2021 could be divided into four clusters, whereas small numbers of MDV‐1 clusters were reported in several other countries (Abd‐Ellatieff et al., 2018; Bayoumi et al., 2021; Mescolini et al., 2020; Ozan et al., 2021). This finding suggests that MDV‐1 circulating in Thailand exhibited a high level of genetic diversity compared to those circulating in some other countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phylogenetic analyses based on the Meq gene demonstrated that MDV‐1 field strains circulating in Thailand between 2013 and 2021 could be divided into four clusters, whereas small numbers of MDV‐1 clusters were reported in several other countries (Abd‐Ellatieff et al., 2018; Bayoumi et al., 2021; Mescolini et al., 2020; Ozan et al., 2021). This finding suggests that MDV‐1 circulating in Thailand exhibited a high level of genetic diversity compared to those circulating in some other countries.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analyses based on the Meq gene demonstrated that MDV-1 field strains circulating in Thailand between 2013 and 2021 could be divided into four clusters, whereas small numbers of MDV-1 clusters were reported in several other countries (Abd-Ellatieff et al, 2018;Bayoumi et al, 2021;Mescolini et al, 2020;Ozan et al, 2021).…”
Section: Phylogenetic and Genetic Analyses Of The Pp38 Genementioning
confidence: 99%
“…In spite of the fact that MD is rarely seen in turkeys, it has been reported in some countries including Netherlands, France, the UK, Israel, Germany, Scotland, Egypt and the USA [ 14 , 22 , 26 , 27 ]. Severe outbreaks of the disease have been reported in commercial turkey flocks in Europe and Israel between 1997 and 2002 [ 1 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…By the means of molecular based methods such as PCR and real–time PCR (qPCR), it is possible to obtain a good indication of pathotype/virulence of the virus owing to the amplification of oncogenicity/pathogenicity related genes followed by sequencing. This also enables us to better understand why protection is not provided in some vaccinated flocks and then develop more efficient vaccines containing the correct pathotype based on molecular characterization [ 14 ]. The PCR analysis of the BamH1-H and BamH1-D regions of the viral genome flanking the 132-bp tandem repeat region is an important criterion that can be used to distinguish between pathogenic and non-pathogenic strains of MDV-1.…”
Section: Introductionmentioning
confidence: 99%
“…They also validated using various Cas13 orthologs simultaneously, which could open the way to target more than one transcript as segmented RNA viruses, including influenza (Yang et al, 2019;Ahmed et al, 2020). Additionally, combining the catalytically inactive Cas13 (dCas13) with the dCas9 version could open new avenues for tracking RNA and DNA simultaneously in DNAreplicating viruses, including herpesvirus models (Yang et al, 2019;Bayoumi et al, 2020aBayoumi et al, , 2021.…”
Section: Mapping Intracellular Localization Of the Viral Genomementioning
confidence: 99%